Internet Banking Technology in Banking Industry (International Journal of Advanced Research in Computer Science, 2017)
Internet banking can improve a bank‟s efficiency and competitiveness, so that existing and potential clients can take advantage of a greater degree of convenience of successful transactions. This increased level of convenience, when combined with new technology, can enlarge the bank‟s target customers. As a result, banking industries are more aggressive in implementing Internet banking capabilities that include sophisticated advancement systems. Internet banking has added another measurement to bank transactions by permitting clients to lead monetary transaction through the Internet. The remarkable rate with which new innovations are, no doubt embraced, the omnipresent and worldwide nature of electronic systems. Banking institutions have taken numerous suitable measures to safeguard security of Internet banking. Nevertheless, it is also essential along with the part of clients to follow some simple, yet important methods to prevent themselves from becoming a victim of computer crackers, who can gain illegal access to the Internet bank accounts. The purpose of the above research paper is to provide detail information about Internet banking technology to the customer. Through this information customer is aware about this service and take a benefit of this service. Keyword: - Internet banking, Delivery channels, Information security, Technological risk, Risk management